(Cryptocurrency as Legal Tender in the Central African Republic: What Challenges and Implications?) - (:unkn) unknown (My University, 2023)
This article examines the challenges of adopting cryptocurrency as legal tender in the Central African Republic (CAR). Cryptocurrencies, which rely on blockchain technology, are decentralized digital currencies that emerged after the subprime mortgage crisis. The global market for these assets is now valued at over $2 trillion. In Africa, the volume of cryptocurrency transactions increased by 1200% between 2018 and 2021, reflecting a growing interest in digital assets. In response, several African countries, including Nigeria, Ghana, and South Africa, are exploring central bank-issued digital currency projects. However, reactions to cryptocurrencies across Africa vary: some countries, like Egypt, have banned them, while others have taken a more open approach.In the Central African Economic and Monetary Community (CEMAC), the Bank of Central African States (BEAC) has expressed concerns about the security of cryptocurrencies and their impact on the banking sector. The CAR's adoption of Bitcoin as official currency in 2022 prompted responses from the BEAC, which recommended conducting a prior study before introducing a central bank digital currency to avoid disrupting the existing economy. Despite these concerns, this initiative in the CAR is seen as a way to open new economic opportunities and promote inclusive growth.The article, however, warns of the risks associated with the lack of a regulatory framework for cryptocurrencies in the CAR. Without regulation, the monetary and banking system, as well as consumers, face various dangers, including extreme volatility of cryptocurrencies, scams, and criminal activities such as money laundering and terrorist financing. It emphasizes the urgent need to regulate this sector to protect users and stabilize the financial system, while also strengthening the capabilities of financial oversight authorities to address the challenges posed by these digital assets.
Keywords: African Research